Exploring the fMRI based neural correlates of the dot probe task and its modulation by sex and body odor. (January 2019) - Hornung, Jonas; Noack, Hannes; Kogler, Lydia; Derntl, Birgit
Highlights: We explored attentional biases via the dot probe task with parallel fMRI. We investigated the modulation of such biases by odor and hormonal states. A consistent and strong attentional bias for fear was detected. Biases were not modulated by odor and hormonal states. No stable neural correlate of attentional biases was found. Abstract: The dot probe task implicitly cues attention via emotional information, an effect which is especially pronounced for threat-related cues. However, several questions remain unexplored. The first one is whether chemosignals like the androgen-derivative androstadienone can influence such attentional biases. Second, few studies have addressed sex differences regarding attentional biases. Finally, the neural correlates of these potential behavioral effects based on functional magnetic resonance imaging (fMRI) are not known. In two experiments we aimed to answer these questions. A total of 159 healthy individuals (58 oral-contraceptive-users, 42 luteal women, 59 men) were tested. In experiment 1 (behavioral study) we examined attentional biases behaviorally, while in experiment 2 (fMRI study) the dot probe task was complemented by fMRI. Our results provide robust evidence that in healthy participants fearful but not angry or happy faces lead to a strong general attentional bias. Elucidating the neural basis of this effects points to an early processing advantage in bilateral thalamus for valid compared to invalid cued fear. However, this finding was limited to those participants with the strongest attentional biases and was not linked to behavioral measures. Furthermore, no consistent sex or group differences existed neither did the putative human chemosignal androstadienone reliably modulate attentional biases or change neural processing.